When policy entrepreneurs drift between levels: The~creation of the International Renewable Energy Agency - Tony Mueller (Global Policy, 2023)
This article examines the crucial role of subnational actors in the diffusion of policy change at the international level, illustrated by the creation of the International Renewable Energy Agency (IRENA). First, the concept of interlevel mobility, which combines the two-level game theory and policy entrepreneurship literature, is introduced. Second, the paper explores how subnational actors navigate between the national, international, and transnational levels, exerting influence and placing their preferences on the political agenda. This research contributes to a more robust theoretical understanding of policy entrepreneurship, provides new insights into the origins of IRENA, and offers valuable guidance for policymakers seeking to foster change, by linking policy change at the international level with subnational actors.
Keywords: 320